Complementarities between Workplace Organisation and Human Resource Management: Evidence from Swiss firm-level panel data - Michael Beckmann; Dieter Kuhn (University of Basel, Center of Business and Economics (WWZ), 2010)
Owing to changes in the business environment, there has been a tremendous adoption of innovative workplace organisation (WO) and human resource (HR) practices during the last few decades. Assuming a holistic perspective on human resource management (HRM), the present study establishes the hypothesis of mutually reinforcing WO and HR practices that, thus, constitute a so-called high-performance work system. Precisely, it is argued that there may be a complementary relationship between a more decentralised way of allocating tasks and decision rights on the one hand and continuing training (or skilled labour), incentive pay or a more intensive use of long-term, as opposed to temporary, employment on the other. This hypothesis is examined empirically using latest nationally representative panel data of about 2,500 firms in Switzerland and applying econometric estimation techniques on the basis of an augmented Cobb-Douglas production function. The estimation results show statistically significant complementarities between the WO and HR practices mentioned above. In addition, socalled innovative HRM systems of mutually reinforcing WO and HR practices increase firm performance significantly. These results are robust to unobserved firm heterogeneity and to the problem of reversed causality.
Keywords: 330; Arbeitsorganisation; Personalmanagement; Unternehmenserfolg; Schweiz